Etyka zawodu księgowego w procesie edukacyjnym - Żuraw, Paweł (Professional Ethics of Book-Keepers in the Educational Process, 2005)
This article presents the issues of teaching the ethical principles in the so called educational process of financial book-keeping services. This issue is worth bringing up for the sake of the signals coming from the area of professional practice, concerning some financiers' and book-keepers' controversial behaviours which appear during their work. The subject is about the recent, widely known scandals concerning the book-keepers' misdeed, which appear not only abroad, but also in our country. It shows the need to take up a discussion concerning the book-keepers' professional ethics, defining what is good and what is bad in terms of their behaviour. In order to decrease such pathologies it is important to concentrate in the educational process not only on the content-related issues in the field of a given domain, but also on the universal values moulding the future staff.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 142-148